2008
DOI: 10.1097/mou.0b013e3282f4ab73
|View full text |Cite
|
Sign up to set email alerts
|

Port site metastases

Abstract: The risk of port site metastases remains low, provided that surgeons rigorously adhere to the principles of oncological surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
15
0
2
Order By: Relevance
“…However, it is logical to assume that morcellation of the specimen increases tumor seeding [5, 6, 15]. The direct dissemination of tumor cells from contaminated material or from extraction with an unclosed bag is well documented [5, 6, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is logical to assume that morcellation of the specimen increases tumor seeding [5, 6, 15]. The direct dissemination of tumor cells from contaminated material or from extraction with an unclosed bag is well documented [5, 6, 15].…”
Section: Discussionmentioning
confidence: 99%
“…When they occur, they often do so in the presence of advanced disease, but it is not uncommon for them to occur in isolation [5, 6]. Concern has been expressed that laparoscopic surgery might adversely affect the long-term outcomes by increasing the risk of port-site and peritoneal seeding.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in that case series, in women with gynecological cancer, the presence of port metastases was most common in high-risk histological types including clear-cell, neuroendocrine cancer or carcinosarcoma [5]. Port-site metastases also seem to be improbable as a result of hematogenous or lymphatic spread [16]. Wound-related factors, such as an alteration in macrophage function and the local and systemic immune response to the pneumoperitoneum, could also be related to port metastases, even though physiology is not yet entirely clarified [17][18][19].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a subcutaneous emphysema could also be related with a potential rise in port metastasis rates [10]. Finally, in cases of incidental finding of malignancy in fibroid specimens, morcellation increases tumor seeding [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews published in 2008 reported 28 cases of port-site metastases following urologic oncology procedures. [2][3][4] The pathophysiological theory surrounding port-site recurrence is debated but currently focuses on tumour seeding into the incisions at the time of surgery by direct tumour contact with the wound, or surgical instruments that have been contaminated. …”
Section: Discussionmentioning
confidence: 99%